Enhancing Fishermen's Economic Stability through Transformative Economic Innovation Education in the Talaud Islands: Sustainable Product and Income Diversification - Julita Inggrine Nelwan; Cornelia Timpal; Jola Silvana Kalangi; Morshe Everly Lumansik; Royke Max Suot; Sjerly Maria Lumi; Lenda Lumenta; Lalira, James (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study proposes a transformative economic innovation education model to strengthen the economic resilience of fishing communities in the Talaud Islands, Indonesia, where livelihoods are highly vulnerable to climate variability and market instability. Given the absence of established diversification initiatives, a participatory multi-criteria decision-making (MCDM) approach was adopted to identify and prioritize feasible product alternatives. The research was conducted in Gemeh District using a mixed-methods design, integrating qualitative insights with quantitative analysis. Focus Group Discussions (FGDs) involving 25 fishermen and five community representatives were conducted to identify eight potential diversification options based on local resource availability and cultural relevance. Subsequently, a decision matrix was constructed using data from 20 active fishermen who evaluated alternatives across seven criteria: initial capital, skill level, weather resilience, income potential, market access, community support, and environmental sustainability. The ANP-EWM-TOPSIS hybrid method was applied to generate a balanced weighting system, combining subjective judgments (via ANP) and objective data variation (via EWM) before the final ranking. Wall décor from marine materials emerged as the top-ranked alternative (CC = 0.817), followed by fermented fish sauce (CC = 0.761), and seaweed farming (CC = 0.739), due to low capital requirements, high weather resilience, and strong community alignment. In contrast, floating net cage aquaculture ranked lowest owing to its high risk and climate vulnerability. These findings demonstrate that land-based, culture-rooted, and waste-utilizing activities offer the most viable pathways for adaptive livelihoods. They concluded that economic resilience can be enhanced through education models that integrate local knowledge, participatory decision-making, and sustainable value addition. This study provides a replicable framework for empowering remote coastal communities in Indonesia and other archipelagic regions.